Implementation Of Law Number 6 Year 2011 Concering Immigration Administrative Actions Against Policies Applicable At The Immigration Office - Achmad Aziz; Ady Arif; Gyan Samladandi Gumay (LEGAL BRIEF, 2021)
The purpose of this research is to explain, analyze, and develop the law in immigration. Indonesia's strategic geographical location has always been a crossroads of world traffic, both air and sea traffic, it cannot be denied because of the strategic location of the Indonesian state, the traffic of foreigners entering or leaving the territory of the Indonesian state is very congested, foreigners entering the country are very dense. Indonesian territory certainly has goals and interests, thus immigration has a function to maintain the upholding of the sovereignty of the Indonesian state. In order to realize the principle of "selective policy" it is necessary to supervise foreigners. This supervision is not only when they enter, but as long as they are in the territory of Indonesia, including their activities. Immigration supervision includes the enforcement of immigration law, both administrative and criminal in nature. To prevent crime or criminal acts from occurring, immigration officers carry out super strict inspections of travel documents owned by people who want to enter or leave Indonesian territory.